An investigation on Turkish military school students: Are there associations among big five personality factors, perceived family environment and hopelessness? - AKBAĞ, MÜGE (ELSEVIER SCIENCE BV, 2010)
The main purpose of this study was to examine whether there were associations among big five personality factors, perceived family environment and hopelessness in a sample of 124 Turkish military school students. In data collecting process, NEO Five Factor Inventory, Hopelessness Scale and Family Environment Questionnaire were used. Research findings revealed that factors having an effect on students' hopelessness were the personality traits (Conscientiousness, Extraversion, Agreeableness, and Neuroticism) and perceived family cohesion. Moreover, the interaction of these variables (personality factors and family environment factors) made stronger effect students' hopelessness level. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Big five personality factors; family environment; hopelessness; adolescence; military school students; SUICIDE